Consequences of Repeated Defoliation on Belowground Bud Banks of Carex brevicuspis (Cyperaceae) in the Dongting Lake Wetlands, China - Chen, Xin-Sheng; Deng, Zheng-Miao; Xie, Yong-Hong; Li, Feng; Hou, Zhi-Yong; Wu, Chao (Frontiers in Plant Science, 2016)
Despite the predominant role of bud banks in the regeneration of clonal macrophyte populations, few studies have examined the way in which clonal macrophytes adjust the demographic features of bud banks to regulate population dynamics in response to defoliation in wetlands. We investigated the density and composition of bud banks under repeated defoliation in the wetland sedge Carex brevicuspis C. B. Clarke in the Dongting Lake wetlands, China. The density and biomass of rhizome buds and shoots did not decrease significantly in response to repeated defoliation over two consecutive years. The composition of bud banks, which consisted of long and short rhizome buds, also did not change significantly in response to repeated defoliation. Nevertheless, the ramet height and the shoot, root, and rhizome mass of C. brevicuspis declined significantly under repeated defoliation. Our findings suggest that bud banks are a conservative reproductive strategy that enables C. brevicuspis to tolerate a certain amount of defoliation. The maintenance of large bud banks after repeated defoliation may enable C. brevicuspis populations to regenerate and persist in disturbed habitats. However, bud bank density of C. brevicuspis might decline in the long term because the amount of carbon stored in rhizome buds and plants is reduced by frequent defoliation.